Digital Living Qur’an: Recitation, Identity, and Social Action in Indonesia’s ODOJ Community - Dede Rodin; Zaenuri; Zulfikar Ali Maulana (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2026)
Living Qur'an scholarship has largely focused on locally bounded communities, whereas digital religion studies have paid limited attention to the reception of sacred texts in online environments. This article examines the One Day One Juz (ODOJ) community in Indonesia as a digital living Qur'an phenomenon, investigating how digitally mediated Qur'anic recitation reshapes religious practice, communal identity, and collective social action. Using a hybrid digital ethnographic approach, the study combines participant observation, semi-structured interviews, and platform document analysis, with data analysed thematically through the proposed Digital Living Qur'an (DLQ) framework. The findings demonstrate that ODOJ institutionalises daily Qur'anic recitation through digital peer accountability, extends Qur'anic practice across interconnected digital platforms, constructs a distinctive symbolic ecosystem, and mobilises nationwide social action despite tensions between ikhlāṣ and riyāʾ, quantity and quality, and democratisation and standardisation. The study argues that these dynamics cannot be fully explained by either conventional Living Qur'an scholarship or digital religion theory alone. It therefore proposes Digital Living Qur'an (DLQ) as a new analytical framework that integrates both perspectives to explain the reception of the Qur'an in digitally mediated communities. Beyond Indonesia, this framework offers a transferable model for analysing comparable digital scripture communities across the Muslim world.